2006
DOI: 10.1007/s10803-006-0124-z
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic and Neuroendocrine Responses to a Psychosocial Stressor in Adults with Autistic Spectrum Disorder

Abstract: Objective of the study was to replicate in adults our previous findings of decreased heart rate and normal endocrine responses to stress in autistic children and to elucidate the discrepancy between autonomic and endocrine stress responses by including epinephrine, norepinephrine, oxytocin and vasopressin measurements. Ten autistic spectrum disorder (ASD) adults were compared to 14 healthy controls in their response to a psychosocial stressor (public speaking). ASD patients showed decreased heart rate, but nor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
120
2
3

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 164 publications
(135 citation statements)
references
References 33 publications
10
120
2
3
Order By: Relevance
“…However, two studies of ASD patients reached different conclusions. One showed higher plasma OXT levels and another suggested no change in plasma OXT levels in autistic individuals [22,23]. The methods of OXT measurement used in these studies were radioimmunoassay (RIA) and enzyme-linked immunoassay (ELISA) without sample extraction.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…However, two studies of ASD patients reached different conclusions. One showed higher plasma OXT levels and another suggested no change in plasma OXT levels in autistic individuals [22,23]. The methods of OXT measurement used in these studies were radioimmunoassay (RIA) and enzyme-linked immunoassay (ELISA) without sample extraction.…”
Section: Discussionmentioning
confidence: 97%
“…Four studies have shown lower plasma OXT levels in children with ASD than in control individuals [15,[18][19][20], two studies have reported higher OXT levels [21,22], and one has reported no overall group difference [23]. Relationships between plasma OXT levels and social behaviors were either not investigated [15,21] or were analyzed in subsets or subtypes of ASD [22,23].…”
Section: Introductionmentioning
confidence: 99%
“…The neurological and endocrine bases for social motivation and affective bonding in infants (e. g., Bowlby 1969 p. 203-204;Moriceau and Sullivan 2005;Grossmann et al 2008) and children (e. g., Bartz and Hollander 2008) have been much less studied than those in mothers (e. g., Strathern et al 2009), though their relevance for understanding mother-child interactions should be no less consequential. Studies of plasma oxytocin levels in autism have yielded unusual results: two studies found lower plasma oxytocin in children with autism (Modahl et al 1998;Green et al 2001), but unexpectedly, oxytocin levels were positively associated with degree of social impairment (Modahl et al 1998); in the single study of adults, autistic individuals showed significantly higher levels of plasma oxytocin than did controls (Jansen et al 2006). Might oxytocin in autistics subserve, to some degree, positive reinforcement of non-social stimuli, or might epigenetically-based reduction of oxytocin receptor expression (Gregory et al 2009) follow from early social-19 interaction deficits?…”
Section: Autism and Attachmentmentioning
confidence: 99%
“…A fourth study reported no overall group differences (16), and a fifth study reported that plasma OXT concentrations are higher in individuals with ASD compared with control participants (17). Relationships between plasma OXT concentrations and measures of social functioning in these small samples were either not analyzed (14,15) or not found (17) or were evident only in subsets of individuals (16). Additionally, one study paradoxically reported inverse relationships between plasma OXT concentrations and social competence in ASD (a negative relationship) and control (a positive relationship) children (13).…”
mentioning
confidence: 94%
“…Three studies reported that plasma OXT concentrations are lower in individuals with ASD compared with control participants (13)(14)(15). A fourth study reported no overall group differences (16), and a fifth study reported that plasma OXT concentrations are higher in individuals with ASD compared with control participants (17). Relationships between plasma OXT concentrations and measures of social functioning in these small samples were either not analyzed (14,15) or not found (17) or were evident only in subsets of individuals (16).…”
mentioning
confidence: 95%